Asia Pacific Breweries: A big gulp for Heineken? - WYATT, Stephen (Institutional Knowledge at Singapore Management University, 2014)
This case is set in December 2012, shortly after the acquisition of Asia Pacific Breweries Limited (APB) by Heineken N.V.. APB is one of the largest brewers in Asia Pacific with a market footprint in 14 countries. This made it an attractive acquisition target for suitors such as Heineken, a global brewer with a strong brand, looking to expand its reach to the younger, high growth markets of Asia. However, the two companies are run very differently in terms of their business models, organisational structure, growth strategies and corporate culture. With the acquisition complete, the task at hand for Heineken is to find a way to manage the differences in business strategies and, consequentially, the divergent corporate cultures.